La construction du rapport à autrui dans les forums de discussion d’adolescents et ses enjeux en situation d’apprentissage scolaire. Le point de vue de l’analyse des interactions - Hassan Atifi; Michel Marcoccia; Nadia Gauducheau (Recherches en Éducation)
Through the analysis of a corpus of on-line interactions (a sample of discursive exchanges from the discussion forum Ados.fr), this paper shows the benefits and the limits of an interactionist approach for understanding the “digital learning subject”. With this point of view, this subject is an “interacting subject” who builds his relationship to others thanks to and in the on-line discursive interactions. This paper permits to describe finely the way complex and paradoxical interpersonal relationships are built: intimate and weakly interpersonal, cooperative and unequal, fun and aggressive. This paper proposes also some remarks about the effects of extra-school digital practices on situations of online learning.